Enhancing EFL Writing Proficiency Among Undergraduates through Gamified Vocabulary Instruction: A Mixed-Methods Investigation of Word Wall Integration - Jesudas, Roseline; Alruwaili, Yasmeen; Gayathrri, Sajeena (Forum for Linguistic Studies, 2025)
This study investigates the impact of Word Wall activities on enhancing the writing skills of undergraduate English as a Foreign Language (EFL) students at Northern Border University. Acknowledging the challenges EFL learners encounter in developing academic and expressive writing, the research explores how visually engaging and interactive vocabulary strategies can facilitate written language acquisition. Utilizing a mixed-methods research design, data were systematically collected from a sample of 120 female students enrolled in Levels 7 and 8. The data collection process included numerical tests to gather measurable data that could be analyzed statistically, along with personal reflections to gain a deeper understanding of individual experiences. The results show a meaningful improvement in students' writing skills, especially in using a variety of words, correct grammar, and clear organization, with average scores of 4.79 and 4.93, and a strong statistical measure of 0.366 (p < 0.001). Participants reported increased motivation, enhanced vocabulary retention, and greater confidence in writing tasks. These findings underscore the pedagogical value of Word Wall activities as an effective approach to developing writing proficiency in EFL contexts. The study recommends integrating vocabulary-focused strategies into writing instruction to support learners in academic and professional communication. Future research may explore the digital implementation of Word Walls to enhance accessibility and engagement.